Tópicos em cosmologia com campos escalares - Santos, José Jamilton Rodrigues dos (2011)
Cosmological models involving scalar fields allow the description of a phase of accelerated cosmic expansion and thus appear as a promising alternative for the study of the cosmic inflation and dark energy. We are interested here in analyzing these cosmological models. In particular, we will explore cosmological solutions based on the first order formalism. The inclusion of this method favors the search for analytic solutions with scalar fields in cosmology, and this is particularly important when we consider the component of nonrelativistic matter (dust) in the presence of dark energy, in order to construct a cosmological model capable of explaining, in good agreement with observational data, the current phase of cosmic acceleration. Considering a regime of Lorentz violation, the use of this method allowed us to verify that new considerations must be implemented so that the inflationary regime can now solve the problem of initial conditions. Another question of interest, which can be addressed with the aid of the first order formalism, takes into account the possibility of the dark energy equation of state parameter to be a constant other than −1 and in this case we get that a lot of fine-tuning is needed, which should be interpreted as strong evidence in favor of a dynamic model of dark energy. We also introduce the so-called deformation method on the slow-roll inflationary models, and we explore this framework in applications of current interest to this branch of research.